ЗБІЛЬШЕННЯ ШВИДКОДІЇ КОНТУРУ СЛІДКУВАННЯ ЗА НАПРУГОЮ НАКОПИЧУВАЛЬНОГО КОНДЕНСАТОРА ТРИФАЗНОГО ПАРАЛЕЛЬНОГО АКТИВНОГО ФІЛЬТРА - Денисенко, К.І.; Кутрань, І.С.; Лесик, В.О.; Мисак, Т.В. (Інститут електродинаміки Національної академії наук України, 2020)
It`s consider the control of a three-phase parallel active filter, which injects a compensating current into the distributed power supply network, due to the presence of a nonlinear load in which there is a distortion of the power parameters. This filter consists of the semiconductor voltage inverter on fully controlled switches, the capacitive storage and the RL-filter. The decomposition of the object of study according to the rates of motion of the dynamic system was performed. The two-dimensional sliding surface is a linear combination of the components of the two-dimensional compensation current error vectors and the first derivative error of this current. To increase the performance of the DC voltage forming process, the modified twisting algorithm to provide asymptotic stability was used. In order to avoid the effect of disturbance in the form of harmonic components of the rectified voltage on the compensating current parameters, the DC voltage and AC current control circuits using a second-mode Chebyshev filter are connected. To confirm the theoretical assumptions, a simulation model was constructed and the results of digital experiments were analyzed. The comparison of the proposed strategy with the traditional PI-regulation by the criteria of the duration of the transition process and the harmonic distortion coefficient in the current consumed by the network is made. References 24, figures 5.